Cognitive Counseling with Modelling Krisna and Bisma to Improve Self Achievement - I Komang Jaya Riana; I Ketut Dharsana; Luh Putu Sri Lestari (Bisma The Journal of Counseling, 2017)
This study aims to Determine the Influence of Cognitive Behavioral Counseling Theory With Lord Krishna Basu Modeling Technique To Improve Self Achievement Through Lesson Study In X-1 Students In Sma Negeri 1 Sukasada. This type of research is quasi-experimental research design with "Nonequivalent Posttest Only Control Group Design". Sampling in this research is done by purposive sampling technique. The sample of this study amounted to 21 students. Data collection method used was self-question questionnaire, Analyzed by t-test analysis technique. The result of this research is get t = 3.323 with 0.003 significance so Ho rejected and Ha accepted. Then it can be concluded that there is influence of cognitive counseling behaviora basu god Krishna modeling technique through self lesson study to improve student achievement of class X-1 in SMA Negeri 1 Sukasada.